Determinação de Cu e Zn em fazendas produtoras de camarão do litoral leste do Estado do Ceará - Santos, Janaína Andrade dos (2005)
The concern with the contamination of heavy metals in farmed shrimp has led to studies with the purpose of measuring the concentration of heavy metals in commercial species, assess potentially hazardous levels from the human health and to supply support for environmental monitoring programs. The production of the shrimp Litopenaeus vannamei is growing fast in the Ceara State. In that way, the objective of is work is to characterize the origin and the distribution of Cu and Zn in three shrimp farms, located at the east coast of the State of Ceara, and the effect of the concentration of these metals in permorfance shrimp. The concentration of Cu and Zn in fertilizers, feed, sediment, suspended material and shrimp was determined by conventional flame atomic absorption spectrophotometry. The concentration of Cu and Zn in fertilizers and chemical additives varied from 0.7 to 3.3 μg/g and from 0.12 to 45.7 μg/g, respectively. In the feed concentrations varied from 13.1 to 79.0 μg/g and from 63.2 to 145.9 μg/g for Cu and Zn, respectively. In pond sediments the average concentrations of Cu varied from 10.3 to 16.5 μg/g and of Zn from 35.1 to 41.1 μg/g. In the suspended material the concentration of Cu varied from 38.4 to 66.8 μg/g whereas Zn was not detectable. In the water the concentration of Cu varied from 6.62 to 7.38 μg/l. In the shrimp the average concentrations of Cu varied from 33.4 to 42.2 μg/g and from 74.0 to 87.2 μg/g in the muscle and the exoskeleton, respectively, while the concentrations of Zn varied from 41.8 to 43.1 μg/g in the muscle and from 52.7 to 55.5 μg/g in the exoskeleton. The intensive farming system of L. vannamei can work as an accumulator of metals in sediments from feeding, chemicals and exuviae. The concentrations of Cu and Zn in the shrimps are below the limits established by the Brazilian legislation for human consumption. However, it was observed that detoxification mechanisms can be acting in those organisms, suggesting that the concentrations animals metabolism at least for Cu already surpass the needs of Cu and could resulting in a decrease in the growth rate the shrimps.